Teachers’ understanding about the characteristics of realistic mathematics education - Cut Morina Zubainur; Rahmah Johar; Rahmi Hayati; M Ikhsan (Journal of Education and Learning (EduLearn), 2020)
The application of Realistic mathematics education (RME) in schools has not satisfied. The efforts of educators to help teachers implement RME are an ongoing process, including by providing examples of learning process through the video lessons. This study aims to investigate teacher understanding of the characteristics of RME through watching video lessons. Three elementary school teachers in Aceh, Indonesia, were involved in this research. Data was collected through questionnaires and semi-structured interviews. Data were analyzed descriptively. The results showed that the teacher did not understand three of the five characteristics of RME. Teachers' understanding of real problems is only limited to the use of concrete objects. The teacher could not identify activities on the video about using models or symbols to scaffold students from concrete to more formal knowledge. The teacher also did not realize that the relationship between mathematical concepts can help students understand mathematics well. The implication of this study is that researchers need to guide the teacher design the learning trajectory before watching learning from other teachers. After watching the whole video lessons, the teacher also needs to be moved to identify important events related to the characteristics of RME in the learning in the video.